The synthesis of a production information system - College of Aeronautics, (Cranfield) (College of Aeronautics, 1965)
Summary This report outlines a proposed information flow system, capable of giving Management the information necessary to effectively control the Production Organisation of Barretts shoe factory in Northampton. The report specifies the functions of each member of the system and assigns responsibilities to these functions and defines the information required to perform them. The system was designed using the philosophy and techniques of Systems Design.